Synthesis and structural characterization of organotin (IV) complexes derived of 4- (Diethylamino) benzoic acid: Cytotoxic assay on human liver carcinoma cells (HepG2) - Win, Yip Foo; Teoh, Siang Guan; Tengku-Muhammad, Tengku Sifzizul; Ha, Sie Tiong; Sivasothy, Yasodha (American-Eurasian Network for Scientific Information, Jordan, 2010)
Organotin(IV) carboxylate complexes derived from 4-(diethylamino) benzoic acid, 4-[N(C2H5)2]C6H4COOH have been successfully synthesized. Two types of diorganotin(IV) complexes {4-[N(C2H5)2]C6H4COO}2(R)2Sn (R= methyl 1, butyl 2), [{4-[N(C2H5)2]C6H4COO(C4H9)2Sn}2O]2 dimer 3 and 4-[N(C2H5)2]C6H4COO(C6H5)3Sn 4 were successfully synthesized and obtained in solid state. The acid and complexes 1-4 obtained were characterized quantitatively using C, H, N and Sn elemental analysis as well as spectroscopic methods such as infrared (FTIR) and nuclear magnetic resonance (1H, 13C & 119Sn NMR). Results of the infrared and NMR spectroscopy on the acid and complexes showed that the coordination took place via oxygen atoms from the carboxylate group. As a result, the tin atom of complex 2 is six-coordinated, complex 4 is four-coordinated and tin atoms of complex 3 are five- and six-coordinated. With the exceptional case the tin atom of complex 1 exhibited five and six coordination in solution state which may be attributed from the dynamic stage or partial disassociation bonding of carboxylate anion. From the cytotoxic assay study, complex 4 revealed a significant result compared to complexes 1-3. © 2010, INSInet Publication.